Effect of Nipah Biochar Pyrolysis Temperature on Composting Pineapple Waste - Hariestya Viareco; Belmis, Restina (Universitas Nusa Bangsa, 2025)
The accumulation of organic waste, such as pineapple peels, requires innovative and sustainable management approaches. Biochar, a carbon-rich material derived from pyrolysis, has been identified as a promising bulking agent to improve composting efficiency. This study investigated the effect of nipah biochar produced at different pyrolysis temperatures (350°C and 450°C) on pineapple peel composting. The characteristics of the biochar were analyzed using XRD and SEM to determine its mineral composition and pore structure, while the composting efficiency was evaluated by measuring pH, moisture retention, and nutrient content. The results showed that the biochar produced at 450°C had a more stable mineral composition—such as graphite, gamma alumina, and quartz—and higher porosity compared to the biochar at 350°C. During the composting process, the 450°C biochar significantly improved pH regulation to the optimal range of 6-7, moisture retention by 50-60%, and compost quality. The decomposition process was also faster, producing compost with higher nitrogen content and C/N ratio compared to the control without biochar. These findings highlight the potential of nipah biochar at high pyrolysis temperatures as an effective bulking agent for sustainable organic waste management.